Impact of Ambient Parameters and Fuel Composition on Performance of Gas Turbine Power Plants - Saad Adam; Seham N. Tawfic; Rawia Abd Al Sattar (African Journal of Advanced Pure and Applied Sciences, 2024)
This study presents an assessment of ambient parameters impact on the performance of gas turbines (GT) power plants. The study was performed on the Benghazi North Combined Cycle Power Plant (BCCPP) through year 2023. The power generation of this plant is running by natural gas fuel for three gas turbine units’ type ’’GT13 E1" with a total capacity of 450 MW, and gas unit module GT13E2 with a capacity of 160 MW. The gas units that were created are operated in a simple cycle system with the possibility of a combined cycle. Efficiency and electric-power output of GT vary according to the ambient conditions. The amount of these variations greatly affects electricity production, fuel consumption and plant incomes. The objective of the present study is to investigate the effect of the ambient parameters such as ambient temperature, flow mass, relative humidity and fuel composition on the performance of gas turbines. It is observed that the power decreases due to reduction in air mass flow rate (the density of the air declines as temperature increases) and the efficiency decreases because the compressor requires more power to compress air of higher temperature. The influence of turbine inlet temperature of the performance of a gas turbine power plant utilized for electricity has been done with the impact parameters. The correlation of these parameters with the turbine inlet temperature showed close dependence on this temperature. On the other hand, gas turbine can run on a wide variety of fuels to produce power. Depending on the fuel composition and resulting properties, specifically the hydrogen–carbon ratio (H/C), so the fuel composition can also affected on the turbine performance.